Investigating socioeconomic disparities of Kangaroo mother care on preterm infant health outcomes - Muhammad Muneeb Hassan; Muhammad Ameeq; M. H. Tahir; Sidra Naz; Laraib Fatima; Alpha Kargbo (Journal of Psychosomatic Obstetrics and Gynecology, 2024)
Several studies have been conducted to examine the complicated relationships between various factors that influence Kangaroo mother care (KMC) for preterm infants. However, the extended socio-economic model has not been seen in any of the previous studies that looked into the factors related to KMC and how it affects the health outcomes of babies born before in our study population. This study examines the various dimensions of KMC implementation and its influence on the health outcomes of premature infants. The current cross-sectional study was carried out in South Punjab, Pakistan, covering both private and public KMC units in obstetrics and gynecology departments. The study included a sample size of 719 patients and was conducted during a period covering 21 September 2022 to 14 October 2023. Multinomial logistic regression analysis is employed to ascertain the factors by using SPSS-26 (SPSS Inc., Chicago, IL). The use of folic acid (OR: 1.44; 95% CI: 0.87–3.11) and factor anemia (OR: 8.82; 95% CI: 1.69–14.59) no significantly correlated with better health outcomes, while environmental toxin exposure had a negative impact (OR: 0.90). The findings underscore the need for comprehensive interventions and policies to bridge socioeconomic gaps, ensuring all preterm infants benefit from KMC.